THE PLACE OF PHILOSOPHY IN SOCIAL LIFE. ANALYSIS AND CONCLUSIONS - Islamkhonova Ominaxon; Rustamova Odina (Western European Studies, 2025)
Philosophy forms one of the bases in which social life is conducted through providing frameworks necessary in developing critical thinking, ethical reflection, and interpreting human existence. It influences cultural norms, political systems, individual behavior, social cohesion, and the progress society makes. This paper focuses on the place of philosophy in social life and contributes to moral values, social justice, and the development of collective identities.
Keywords: philosophy; social life; ethics; culture